2013
DOI: 10.1371/journal.pone.0056291
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Terminal EPIYA Phosphorylation Motifs in Helicobacter pylori CagA Contributes to IL-8 Secretion, Irrespective of the Number of Repeats

Abstract: CagA protein contributes to pro-inflammatory responses during H. pylori infection, following its intracellular delivery to gastric epithelial cells. Here, we report for the first time in an isogenic background, on the subtle role of CagA phosphorylation on terminal EPIYA-C motifs in the transcriptional activation and expression of IL-8. We utilized isogenic H. pylori mutants of P12 reference strain, expressing CagA with varying number of EPIYA-C motifs and the corresponding phosphorylation defective EPIFA-C mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 55 publications
(94 reference statements)
4
36
0
Order By: Relevance
“…MMP-3 protein expression in total cell lysates, as well as in culture supernatants (representing the secreted form), was found to be dependent on CagA phosphorylation in EPIYA-C repeats. Similarly, the higher the number of EPIYA-C repeats in the expressed CagA protein, the greater the MMP-3 transcriptional activation observed, in line with our previous observations of induction of a more intense scattering and elongation phenotype in the presence of an increasing number of EPIYA-C repeats [43]. Similar results with respect to increased MMP-3 expression were observed when we infected the human gastric adenocarcinoma cell line MKN45 with bacterial strains expressing CagA protein with functional EPIYA-C motifs, although endogenous expression of MMP-3 was also detected under uninfected conditions in this cell type.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…MMP-3 protein expression in total cell lysates, as well as in culture supernatants (representing the secreted form), was found to be dependent on CagA phosphorylation in EPIYA-C repeats. Similarly, the higher the number of EPIYA-C repeats in the expressed CagA protein, the greater the MMP-3 transcriptional activation observed, in line with our previous observations of induction of a more intense scattering and elongation phenotype in the presence of an increasing number of EPIYA-C repeats [43]. Similar results with respect to increased MMP-3 expression were observed when we infected the human gastric adenocarcinoma cell line MKN45 with bacterial strains expressing CagA protein with functional EPIYA-C motifs, although endogenous expression of MMP-3 was also detected under uninfected conditions in this cell type.…”
Section: Discussionsupporting
confidence: 91%
“…It is widely accepted that, after adhesion of H. pylori to gastric epithelial cells, the bacterial oncoprotein CagA is translocated through the bacterial type IV secretion system, and after intracellular phosphorylation by mammalian kinases on EPIYA C-terminal phosphorylation motifs, induces the appearance of a scattering and elongation phenotype [8,9,15,[43][44][45][46][47][48][49]. Hierarchical phosphorylation of CagA by Src and Abl kinases on repetitive EPIYA sequences located at the C-terminus of the protein, plays a pivotal role in this phenotypic change [8,9,47,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the CagA protein itself plays a role in direct activation of NF-jB and other inflammatory pathways is still debated. Kang et al [9] did report direct activation of NF-jB by CagA, and similarly, Papadakos et al [10] demonstrated a novel IL-8 upregulation and secretion that was dependent on the presence of the terminal CagA EPIYA motif [10]. However, the observed effects of CagA were rather small.…”
Section: The Gastric Epithelium Acts As First Line Of Defensementioning
confidence: 95%
“…39 This occurs because the presence of EPIYA-C segments of the CagA protein appears to significantly contribute to the transcriptional activation of IL-8, through activation of NF-kB (factor nuclear kappa B). 40 IL-8 plays a crucial role by chemo attracting and activating neutrophils to the site of infected gastric mucosa. 41 Batista et al showed that increasing of the number of segments EPIYA-C was associated with precancerous gastric lesions and with decreased serum levels of pepsinogen I, which reflects the functional and morphological status of the gastric mucosa.…”
Section: Influence Of Cytokines Genes Polymorphisms In the Gastric DImentioning
confidence: 99%